THE JEWELLED TABLE COOKING, EATING & ENTERTAINING THE MIDDLE EASTERN WAY - Kehdy, Bethany (Hardie Grant Books, 2018)
Middle Eastern food is meant for sharing, and in The Jewelled Table, Bethany Kehdy departs from the common mezze theme to explore the way locals cook, eat and entertain at home. The book and its chapters are ordered in the style one goes about 'jewelling' a table in the Middle East, whether for everyday meals or for celebratory feasts, always much inspired by the seasons and the ritual of hospitality. Featuring over 100 ancient and modern recipes - including appetisers, drinks, show-stopping mains, fuss-free sweets and more - and menu plans that take the stress out of entertaining, Bethany illustrates that with a few key ingredients, this is the perfect fit for every occasion. With her signature flair for creative and tantalising flavour combinations, Bethany introduces dishes such as Winter's tabbouleh, Orange blossom chicken barida, Charred asparagus & dried lime soup and more. This is Middle Eastern food like you've never seen it. Set against the backdrop of beautiful location shots, and Bethany's charming anecdotes with a lens on history, lineage and etymology, The Jewelled Table is an essential cookbook for anyone who loves the flavours of the Middle East.